2015
DOI: 10.7554/elife.07398
|View full text |Cite
|
Sign up to set email alerts
|

Crumbs is an essential regulator of cytoskeletal dynamics and cell-cell adhesion during dorsal closure in Drosophila

Abstract: The evolutionarily conserved Crumbs protein is required for epithelial polarity and morphogenesis. Here we identify a novel role of Crumbs as a negative regulator of actomyosin dynamics during dorsal closure in the Drosophila embryo. Embryos carrying a mutation in the FERM (protein 4.1/ezrin/radixin/moesin) domain-binding motif of Crumbs die due to an overactive actomyosin network associated with disrupted adherens junctions. This phenotype is restricted to the amnioserosa and does not affect other embryonic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 179 publications
(255 reference statements)
8
48
0
Order By: Relevance
“…Mbs dephosphorylates Moesin in the AS and not in the epidermis, suggesting that this is a tissuespecific effect. Interestingly, it has recently been reported that an AS-specific function of Crumbs involving its FERM binding domain also affects actomyosin contractility and adhesion in this tissue (Flores-Benitez and Knust, 2015). In that work, a phosphomimetic form of Moesin was able to rescue the defects caused by this particular Crumbs mutant.…”
Section: Mbs As Coordinator Of Cytoskeletal Activity and Adhesionmentioning
confidence: 50%
“…Mbs dephosphorylates Moesin in the AS and not in the epidermis, suggesting that this is a tissuespecific effect. Interestingly, it has recently been reported that an AS-specific function of Crumbs involving its FERM binding domain also affects actomyosin contractility and adhesion in this tissue (Flores-Benitez and Knust, 2015). In that work, a phosphomimetic form of Moesin was able to rescue the defects caused by this particular Crumbs mutant.…”
Section: Mbs As Coordinator Of Cytoskeletal Activity and Adhesionmentioning
confidence: 50%
“…Fourth, we still do not understand what directs the location of an actomyosin pulse. Fifth, we advocate searches for proteins outside of the core actomyosin machinery, for example aPKC (David et al, 2013) and Crumbs (Flores-Benitez et al, 2015), that impinge on actomyosin dynamics. Finally, we are excited about using the newest generation of in vivo biomechanical sensors, like lipid droplets embedded in epithelia (Campàs et al, 2014) or single-walled carbon nanotubules (Tan et al, 2016) that can provide direct measurements of the material properties of cells and tissues experiencing dynamic actomyosin contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the hypothesis that the Sdt-Crb complex is specifically required in polarizing cells undergoing fast AJ turnover, whereas in polarized cells biosynthetically stable AJs make Sdt-Cbr dispensable. Interestingly, DE-CadASSA or DE-CadS4A-αCat did not rescue Baz localization in amnioserosa cells in crb KO or sdt KO mutant embryos (data not shown), suggesting that the Sdt-Crb complex acts through mechanisms independent of AJ stability to maintain polarity in these actively constricting cells (David et al, 2010;Flores-Benitez and Knust, 2015;Harden et al, 2002).…”
Section: Conserved Serine Residues Regulate the Biosynthetic Turnovermentioning
confidence: 99%